Assessing the Impact of Chronic Rhinosinusitis on Intraocular Pressure and Glaucoma Progression, A Clinical Study - Saira Bano, Irshad Ali, Salman Ahmed Niaz Mangrio, Rehan Moinuddin Shaikh, Ahsan Qureshi, Javed Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Chronic rhinosinusitis (CRS) is a chronic inflammatory condition of the paranasal sinuses with systemic effects outside the sinonasal cavity. There is emerging evidence of a possible association between CRS and ocular disorders, including elevated intraocular pressure, and glaucoma progression. Aims and Objectives: The purpose of this study was to determine the effect that chronic rhinosinusitis has on intraocular pressure and glaucoma progression. It wanted to assess ocular parameters between CRS patients and healthy controls. The aim was to find clinical correlation and risk implication in CRS cases for glaucoma. Methodology: A prospective, observational study was done in 100 adult participants equally divided into CR and control groups. ENT assessments were performed in detail: nasal endoscopy and CT-based Lund-Mackay scoring. IOP was measured, OCT, visual field testing and optic disc were evaluated. Statistical analysis of data was done using SPSS software and p < 0.05 was considered significant. The objective of this study was to see if there are correlations between severity of CRS and ocular changes associated with glaucoma. Results: Intraocular pressure (IOP) was significantly higher in the CRS group at baseline (18.9 ± 2.1 mmHg) and after six months (20.1 ± 2.4 mmHg) compared to controls (17.3 ± 1.8 and 17.5 ± 2.0 mmHg, p < 0.05) respectively. In addition, the early glaucomatous changes were indicated by the CRS group with increased cup to disc ratio and decreased retinal nerve fiber layer (RNFL) thickness. Comparisons of the mean deviation in the visual field showed worse visual field mean deviation in CRS patients (p < 0.01). In addition, 16 per cent of controls but 32 per cent of CRS patients required anti-glaucoma medications. These findings may indicate a relation between CRS and glaucoma progression and would call for more frequent ophthalmologic monitoring. Conclusion: This study showed that chronic rhinosinusitis has a strong association with elevated intraocular pressure and, early, glaucomatous changes. Inflammatory or anatomical mechanisms may contribute to the progression of glaucoma through CRS. Periodic follow up for glaucoma screening in CRS patients is advised. Keywords: Intraocular pressure, Glaucoma, Chronic Rhinosinusitis, Inflammatory, Glaucomatous